Phenotypical Changes of Hematopoietic Stem and Progenitor Cells in Sepsis Patients: Correlation With Immune Status? - Wang, Ping; Wang, Jun; Li, Yi-hao; Wang, Lan; Shang, Hong-cai; Wang, Jian-xun (Frontiers in Pharmacology, 2021)
Background: Sepsis is life-threatening organ dysfunction associated with high risk of death. The immune response of sepsis is complex and varies over time. The immune cells are derived from hematopoietic stem and progenitor cells (HSPC) which can respond to many infections. Our previous study found that sepsis causes HSPC dysregulation in mouse. But few studies have previously investigated the kinetics of HSPC and its contribution to immune system in sepsis patients. Purpose: We aimed to identify the kinetics of HSPC and its contribution to immune system in sepsis patients. Methods: We enrolled 8 sepsis patients and 5 healthy control subjects. Peripheral blood (PB) samples from each patient were collected for 3 times: on the first, fourth and seventh day, while once from each healthy control subject. Peripheral blood mononuclear cells (PBMC) were isolated by density centrifugation and stained with cocktails of antibodies. Populations of HSPC and its subpopulation were analyzed by flow cytometry. Immune cells were characterized by flow cytometry and blood cell analysis. Correlations between HSPC and immune cells was analyzed using pearson correlation test. Results: We found that the frequency of HSPC (CD34+ cells and CD34+CD38+ cells) in sepsis patients on day 4 was significantly higher compared to the healthy control. The most pronounced changes in subpopulation analysis is the frequency of common myeloid progenitors (CMP; CD34+CD38+CD135+CD45RA−). But no difference in the immunophenotypically defined hematopoietic stem cells (HSC; CD34+CD38−CD90+CD45RA−) in sepsis patients was observed due to rare HSC number in PB. The number of PBMC and lymphocytes were decreased, whereas the white blood cells (WBC) and neutrophils count were increased in sepsis patients. Importantly, we found a negative correlation between CD34+ on day 1 and WBC and lymphocytes on day 4 from correlation analysis in sepsis patients. Conclusions: The present study demonstrating that the HSPC and its subpopulation of sepsis patients were expansion. Importantly, the changes of HSPC at early timepoints in sepsis patients have negative correlations with later immune cells. Our results may provide a novel diagnostic indicator and a new therapeutic approach.